Association between oxidative balance score and all-cause, CVD and respiratory-related mortality in the US older adults of asthma patients with diabetes - Liu, Chang; Liang, Dan; Xiang, Guoan; Zhao, Xuanbo; Xiao, Kun; Xie, Lixin (Frontiers in Nutrition, 2025)
BackgroundThis study aims to investigate the correlation between oxidative balance score (OBS) and all-cause, cardiovascular disease (CVD) and respiratory-related mortality within a cohort that includes older asthma patients with diabetes.MethodsData from the National Health and Nutrition Examination Survey (NHANES) spanning from 2001 to 2018, which included 611 participants, were analyzed. Mortality outcomes were determined by linking the data to National Death Index (NDI) records through December 31, 2019. Cox regression modeling was employed to examine the relationship between OBS and all-cause, CVD and respiratory-related mortality. Restricted cubic splines (RCS), subgroup analyses and interaction tests were also conducted in this study.ResultsOver a median follow-up of 78.96 months, there were 216 all-cause deaths and 57 CVD-related deaths. A significant negative association was found between the OBS and all-cause and CVD mortality. We did not observe OBS could reduce respiratory-related mortality in older asthma patients with diabetes. RCS analysis indicated a linear and inverse association between the OBS and all-cause and CVD mortality. Subgroup analyses and interaction tests indicated the negative association between OBS and CVD mortality was significantly influenced by alcohol consumption.ConclusionIn this sample, higher OBS was associated with lower all-cause and CVD mortality risks. These findings stressed the importance of infection status in assessing oxidative balance’s impact on health.